DNA Phosphorothioate Modification Plays a Role in Peroxides Resistance in Streptomyces lividans - Dai, Daofeng; Du, Aiqin; Xiong, Kangli; Pu, Tianning; Zhou, Xiufen; Deng, Zixin; Liang, Jingdan; He, Xinyi; Wang, Zhijun (Frontiers in Microbiology, 2016)
DNA phosphorothioation, conferred by dnd genes, was originally discovered in the soil-dwelling bacterium Streptomyces lividans, and thereafter found to exist in various bacterial genera. However, the physiological significance of this sulfur modification of the DNA backbone remains unknown in S. lividans. Our studies indicate that DNA phosphorothioation has a major role in resistance to oxidative stress in the strain. Although Streptomyces species express multiple catalase/peroxidase and organic hydroperoxide resistance genes to protect them against peroxide damage, a wild type strain of S. lividans exhibited two-fold to 10-fold higher survival, compared to a dnd- mutant, following treatment with peroxides. RNA-seq experiments revealed that, catalase and organic hydroperoxide resistance gene expression were not up-regulated in the wild type strain, suggesting that the resistance to oxidative stress was not due to the up-regulation of these genes by DNA phosphorothioation. Quantitative RT-PCR analysis was conducted to trace the expression of the catalase and the organic hydroperoxide resistance genes after peroxides treatments. A bunch of these genes were activated in the dnd- mutant rather than the wild type strain in response to peroxides. Moreover, the organic hydroperoxide peracetic acid was scavenged more rapidly in the presence than in the absence of phosphorothioate modification, both in vivo and in vitro. The dnd gene cluster can be up-regulated by the disulfide stressor diamide. Overall, our observations suggest that DNA phosphorothioate modification functions as a peroxide resistance system in S. lividans.